PENDEKATAN KONSTRUKTIVISME DALAM PROSES PEMBELAJARAN IPS - Muhammad Nur (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
The research results show that; 1) The constructivism approach in social studies learning is considered to be able to bridge the gap between social studies learning in the classroom and the development of social dynamics in society. The flood of information and scientific progress should be balanced with continuous innovation in the learning process. Therefore, it is the teacher who holds the primary responsibility. Teachers can implement a constructivist learning approach with the following learning implementation procedures: (a) giving independent assignments to students; (b) make presentations using power point media; (c) presentations and discussions by students guided by the teacher; and (d) activities to access various learning resources in the community. 2) Teachers can further develop IPS learning with a constructivist approach while minimizing obstacles in the field. The steps that can be taken are as follows: a) students explore social issues; (b) students identify and formulate actual social problems; (c) students explore information from various learning sources; (d) students determine several alternative solutions to problems; (e) students formulate solutions to social problems in the field; (f) students determine an action plan to get support from the surrounding community; (g) students make scientific work on social issues; (h) students present findings of social problems in group discussions in class; and (i) teachers and students reflect on learning experiences